2010
DOI: 10.2478/v10026-010-0020-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of pyrolysis residue from waste materials in black coal flotation

Abstract: Application of pyrolysis residue from waste materials in black coal flotation The paper deals with the verification of the floatability of pyrolytic oils, which were obtained through the pyrolysis of waste, namely mixed plastics, tyres and waste rubber in combination with black coal from Lazy Mine, and classical collector Montanol 551 in black coal flotation. Black coal from ČSA OKD, a.s. coal preparation plant was used for flotation tests. The results imply that it is possible to produce collectors fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…In addition, a peak at 1602 cm −1 corresponding to stretching vibrations of the C=C bond found in alkenes was noticed in sample PO18-H-0.09 [48]. The presence of this bond in the test sample may be indicative of poor polymerization of the oil in the oil matrix [40]. EDS X-ray analysis of the solids showed that they consisted mainly of carbon, oxygen, and silicon.…”
Section: Oil Blocks Based On Post-pyrolysis Oilsmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition, a peak at 1602 cm −1 corresponding to stretching vibrations of the C=C bond found in alkenes was noticed in sample PO18-H-0.09 [48]. The presence of this bond in the test sample may be indicative of poor polymerization of the oil in the oil matrix [40]. EDS X-ray analysis of the solids showed that they consisted mainly of carbon, oxygen, and silicon.…”
Section: Oil Blocks Based On Post-pyrolysis Oilsmentioning
confidence: 94%
“…The first is located at a wave number of 1055 cm −1 and corresponds to bending vibrations of C-H bonds present in aromatic compounds. The peaks present at 777 and 694 cm −1 originate from the bending vibrations of the C-H bonds of single-substituent aromatic compounds [38][39][40]. For samples PO18-H-0.09 and PO24-H-0.135, there are distinct peaks at 2942, 2918, and 2852 cm −1 corresponding to stretching vibrations of C-H bonds.…”
Section: Oil Blocks Based On Post-pyrolysis Oilsmentioning
confidence: 98%
See 1 more Smart Citation
“…C-H deformation vibrations occur at wave numbers of 776-781 cm −1 . The peaks observed around 690 cm −1 originate from the bending vibrations of C-H bonds in mono-substituted aromatic compounds [40][41][42]. Peaks in the range of 570-620 cm −1 originate from the asymmetric and symmetric stretching vibrations of the Zn-O bonds in the structure of zinc oxide.…”
Section: Sorption and Photocatalytic Effect Of Composite Materialsmentioning
confidence: 99%